Texturisation of Single Crystalline Silicon Solar Cell - M.Z.F. Zaidi;; N.F.A. Ahmad Iqbal;; T.T. Loo (Universiti Sains Islam Malaysia, 2024)
Corruption has appeared throughout the land and sea by (reason of) what the hands of people have earned so He may let them taste part of (the consequence of) what they have done that perhaps they will return (to righteousness). [30:41]. Rigorous and over exploitation of oil reserves have caused multiple destruction to land and sea; both in exploration and application of oil. Alternative energy source such as solar power is no longer desirable, it is crucial. The potential of solar cells have not been fully tapped due to lack of energy conversion efficiency. There are three importance mechanisms in producing high efficiency cells to harvest solar energy; reduction of reflectance, light trapping in the cell and higher light absorption. The work carried out shows studies conducted in surface texturisation of single crystalline silicon solar cells using wet chemical etching techniques. Two etching types are applied; alkaline etching (K0H:IPA:DI) and acidic etching (HF:HN03:DI). The alkaline solution resulted in anisotropic profile that leads to the formation of inverted pyramids. While acidic solution formed circular craters along the front surface of silicon wafer. This surface modification leads to the reduction of light reflectance from the surface and thereby increases the short circuit current and conversion rate of the solar cells. The work carried out already won award in ENVEX2010, and produced a paper in IEEE conference.